Drugstore Beetle, Stegobium paniceum (L.) (Insecta: Coleoptera: Anobiidae) - Brian J. Cabrera (EDIS)
This document is EENY-228, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2001.